2008
DOI: 10.1586/14779072.6.2.235
|View full text |Cite
|
Sign up to set email alerts
|

Bicuspid aortic valve: clinical approach and scientific review of a common clinical entity

Abstract: Bicuspid aortic valve (BAV) disease is becoming increasingly respected by clinicians. This enhanced appreciation is based on recognition of how common and virulent this disease really is. This disease is now known to be the most common congenital lesion affecting the human heart (with potential competition in frequency posed by mitral valve prolapse). It is estimated that the BAV lesion alone accounts for more morbidity and mortality than all the other congenital cardiac lesions combined. Many authorities feel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 91 publications
0
76
0
2
Order By: Relevance
“…BAVs may result from the fusion of any leaflet, although in humans, right–left fusion is most common 34. The process of leaflet fusion is currently not well understood because leaflet fusion may occur early in cushion development or later during valve remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…BAVs may result from the fusion of any leaflet, although in humans, right–left fusion is most common 34. The process of leaflet fusion is currently not well understood because leaflet fusion may occur early in cushion development or later during valve remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…(3,8,9) It is especially true for patients with a bicuspid aortic valve as fetal congenital heart disease occurs in ±4% of women with congenital AS. Fetal ultrasound is suggested when the mother has a bicuspid aortic valve.…”
Section: Pre Pregnancy Evaluation and Managementmentioning
confidence: 99%
“…According to population-based studies, a BAV is estimated to be present in 1-2% of the population (36)(37)(38). Concomitant bicuspid aortopathy is common as well, although the exact estimates vary greatly from 20% to 84% (Figure 8) (38).…”
Section: Bicuspid Aortic Valvementioning
confidence: 99%
“…It is important to remember that BAV-related aortic aneurysms are a major causative factor for aortic dissection, which usually occurs long before a clinically evident aortic stenosis will develop (37). At the same time, some recent studies have shown that the long-term survival for patients with a BAV is not much different from a matched control population (40).…”
Section: Bicuspid Aortic Valvementioning
confidence: 99%